Efeitos da castanha-do-Brasil (Bertholletia excelsa H.B.K.), família Lecythidaceae, sobre parâmetros comportamentais, nutricionais e bioquímicos na prole de ratas obesas - Apolinário, Lilian Fioravanso (2021)
Maternal obesity has long-term consequences for offspring as a predisposition to metabolic and neurodevelopmental disorders. The brazil nut oilseed (Bertholletia excelsa H.B.K.), family Lecythidaceae, native to the Amazon region, is a rich source of nutrients, among them the mineral selenium. Considering that brazil nut is capable of modulating inflammation, the objective of this work was to evaluate its effect on behavioral, nutritional and biochemical parameters on the offspring of obese rats. Wistar rats were used at 60 days, which were randomly divided into groups with water and ad libitum ration: control with standard diet (mCTL) - (Nuvilab CR-1, Nuvital, PR-Brazil) -; brazil nut with a standard diet added brazil nut (mCTL/CST); high fat with standard diet added with fat (mHPL) and high fat brazil nut with high fat diet added with brazil nut (mHPL/CST), ending at 21st. postpartum day (weaning). Male offspring received standard diet and water ad libitum, with biometric and food consumption checks being carried out; at 30 and 90 days, they underwent elevated plus-maze (LCE); object recognition task (TRO) and marble burying task. The determination of serum selenium, biochemical dosages and oxidative stress markers were performed at 90 days. The physicochemical analysis of aflatoxins and the determination of the selenium content of Brazil nuts (from Itaúba-MT) were carried out. Data were statistically analyzed by twoway analysis of variance (ANOVA), followed by post hoc Tukey, when appropriate, or the Kruskal-Wallis test, followed by the Dunn's test. Differences between groups were considered significant when p<0.05. Brazil nuts had a selenium content of 3.95 + 0.020 mg/kg (2018/2019 crop) and 3.76 + 0.015 mg/kg (2019/2020 crop). Maternal consumption of a high-fat diet led to the condition of obesity (mHPL and mHPL/CST). The pHPL/CST group (offspring of the mHPL/CST group), in young and adult age, and the pHPL group (offspring of the mHPL group), in adulthood, were obese. There was an increase in food consumption in the pHPL and pCTL/CST groups (offspring of the mCTL/CST group). There was a decrease in consumption relative to body weight gain in the pCTL/CST, pHPL and pHPL/CST groups. No difference was observed regarding anxiety behavior, assessed by LCE and marble burying task. The pHPL group, in young and adult age, showed impairment in memory behavior assessed by TRO, with prevention of this effect, in young offspring, in the short-term memory test for the pCTL/CST and pHPL/CST groups. A reduction in serum selenium levels was observed in the pHPL group. There was a serum reduction of the catalase enzyme in the pCTL/CST, pHPL and pHPL/CST groups, but there was no increase in lipid peroxidation or protein carbonylation. No differences were observed regarding glycemic level and lipid profile. The pHPL and pHPL/CST groups showed increased alanine aminotransferase (ALT). The supplementation with Brazil nuts in the maternal diet prevented damage to the neurodevelopment of young and adult offspring.